Prevalence of hearing impairments in landmine survivors less than 18 years - M. Heydarian Moghaddam; S.H. Seyyed Hosseini Davarani; H. Shokouhi; S.A. Mirsadeghi; Gh.H. Arab Sheybani; M. Masoumi; R. Amouyi Khorshidi; E. Modirian; B. Mousavi; M.R. Soroush; M. Hosseini (Afarand Scholarly Publishing Institute, 2015)
Aims: Sudden terrible sound, like the sound of landmine explosion, can rupture the eardrum, disruption of the ossicular chain, ear nervous system disorders and in some cases causes complete deafness. Accordingly, this study aimed to data collection and assesses the hearing health of Iranian landmine survivors less than 18 years old. Methods: All mine survivors less than 18 with hearing disorder enrolled and after obtaining demographic information, hearing status, clinical and treatment data were evaluated by an ENT specialist. Frequencies were reported as number, percentage and mean ± SD. Results: About one third of landmine survivors suffered from hearing disorders that their average age was 16.13±2.05 years and mean duration of hearing loss was 6.7±2.5 years. The most common negative side issue was headache, 81.3%. More subjects were in trouble in crowded environments with high frequency sound (65%) and tinnitus was a common problem among them (87%). Sensorineural hearing loss had a frequency near to 50% for both right and left ear. No significant association was found between duration of injury and degree of hearing loss. The mean number of speech perception threshold test was less than half of the standard value and the mean score of ability to separate speech was within normal limits. Conclusion: Sudden exposure to sound like landmine explosion may cause hearing disorders such as hearing loss and side problems such as headache, dizziness, and tinnitus that are able to dramatically affect the quality of life. The prevalence of hearing impairments in young survivors of landmine explosion is very high and long after the casualties, some of them continue to suffer from hearing problems. Due to the sensitivity age of study group, further studies in this regard and regular checkups seem to be necessary.